Prevention before intervention: introducing mindfulness-based social-emotional learning in higher education institutions across the United Arab Emirates - Kassie, Seada A. (Frontiers in Education, 2023)
This communicative piece seizes the UAE’s growing commitment to implement its strategy for talent attraction and retention as well as to increase mental health awareness, prevention, and intervention practices as an opportunity to propose a reform across institutions providing higher education in the UAE. The article discusses the prevalence of stress and anxiety disorders in higher education and among the general youth in the UAE, potential reasons for such high rates of prevalence, the government’s commitment towards awareness and prevention of mental health disorders, the importance of introducing lessons and training in mindfulness-based social-emotional learning (MBSEL), the relevance of social-emotional competencies for employability and adaptability in the rapidly evolving workplace, and practical measures that can be taken at the institutional level within the UAE context.